Sosialisasi dan Pembentukan Pusat Informasi dan Konseling Remaja (PIK-R) Desa Kecis, Selomerto - Astuti, Elvina Tri; Wiwid Muzayyanah; Nihaya Zahra Novitasari; M. Katami Usaqil Muna; Hidayatus Sibyan (CV. Nature Creative Innovation, 2023)
Abstract: Center for Information and Counseling for Youth (PIK-R) is one of the activities included in the GenRe (Generation Planning) program which was indeed developed by the BKKBN which is managed from, by and for youth/students to provide information and counseling services about age maturity marriage, eight family functions, Triad KRR (Life Skill), advocacy skills and IEC. Socialization activities and the formation of the Youth PIK have the aim of forming and organizing the Youth PIK organization itself and training youth in the village of Kecis to participate in organizational activities, youth can also develop and increase their potential through the PIK-R organization. The method or technique used in this activity is education. The results achieved include the formation of the PIK-R KUSUMA Kecis Village and organizational structure.